The bear, the piano, the dog, and the fiddle - Litchfield, David (Clarion Books, Houghton Mifflin Harcourt, 2019)
Hugo the dog becomes the star of an all-animal band after learning to play his best friend Hector's fiddle, and despite Hector's jealousy, remains grateful to the man who gave him his start.